2021
DOI: 10.1016/j.trsl.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiling in Diabetic Kidney Disease

Abstract: The microRNAs (miRNAs) that can regulate diabetic kidney disease (DKD) have not been fully characterized. The aim of this study was to identify the miRNAs that affect DKD and could be used as specific biomarkers or therapeutic agents. First, kidney tissues from two DKD mouse models and control mice were screened for differences in miRNA expression by microarray analysis followed by quantitative real-time reverse transcription-PCR. Six miRNAs were differentially expressed from controls in both DKD mouse models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The expression level of one miRNA (miRNA-503-5p) that we observed was differentially expressed in kidneys of the present study's age-dependent renal impairment mice was also evaluated in kidneys of other model mice of kidney diseases by qRT-PCR: a model of diabetic kidney disease (DKD) (db/db mice) (15), a model of renal fibrosis caused by UUO (6), a model of acute kidney injury (ischemiareperfusion injury; IRI) (16), a model of focal segmental glomerulosclerosis (FSGS) generated by adriamycin intravenous injection (17), and a model of immunoglobulin A nephropathy (HIGA/NscSlc) (18). The expression level of miRNA-503-5p differed between the DKD, UUO, and FSGS mice and the respective groups of control mice (Figures 4A-C), while it did not differ between the IRI and HIGA mice and the respective control groups (Figures 4D,E).…”
Section: Mirna-503-5p Expression In the Kidney Of Other Model Micementioning
confidence: 97%
“…The expression level of one miRNA (miRNA-503-5p) that we observed was differentially expressed in kidneys of the present study's age-dependent renal impairment mice was also evaluated in kidneys of other model mice of kidney diseases by qRT-PCR: a model of diabetic kidney disease (DKD) (db/db mice) (15), a model of renal fibrosis caused by UUO (6), a model of acute kidney injury (ischemiareperfusion injury; IRI) (16), a model of focal segmental glomerulosclerosis (FSGS) generated by adriamycin intravenous injection (17), and a model of immunoglobulin A nephropathy (HIGA/NscSlc) (18). The expression level of miRNA-503-5p differed between the DKD, UUO, and FSGS mice and the respective groups of control mice (Figures 4A-C), while it did not differ between the IRI and HIGA mice and the respective control groups (Figures 4D,E).…”
Section: Mirna-503-5p Expression In the Kidney Of Other Model Micementioning
confidence: 97%
“…4 miRNA has a critical role in maintaining normal organ development and homeostasis by partially complementing the specific mRNA 3′-UTR to regulate the expression of downstream target proteins and then participate in basic biological processes. 5 A previous study suggested an association between miR-124 and the onset of kidney disease and diabetes. 6,7 miR-124 is abnormally expressed in patients with renal disease and ischemic stroke complicated with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA, a non‐coding single‐stranded RNA molecule with a length of about 20–24 bp nucleotide, participates in the progression of chronic kidney disease by regulating mitochondrial function 4 . miRNA has a critical role in maintaining normal organ development and homeostasis by partially complementing the specific mRNA 3′‐UTR to regulate the expression of downstream target proteins and then participate in basic biological processes 5 . A previous study suggested an association between miR‐124 and the onset of kidney disease and diabetes 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, most evidence in this attractive research area is based on adult [ 36 , 37 , 38 , 39 , 40 ] and in vitro studies [ 27 , 28 , 41 , 42 ], while similar pediatric data are still limited [ 43 , 44 , 45 , 46 , 47 ]. Due to the urgent need for early identification of DN and of the fragmentariness of data in the field in childhood, we attempted to provide a comprehensive pediatric overview on the challenging role of miRNAs in DN.…”
Section: Introductionmentioning
confidence: 99%